A revista EXAME: a mídia de negócios numa dimensão política - Frederico, Ronaldo (2015)
This investigation is substantiated in the concept of "Symbolic Enterprisation" (SE)' formulated by this author, that points out the executive and entrepreneur that hold the power to expand the values and principles which guide the corporate activities. As symbolic representatives of the capitalist economic's reality, with interests and specific needs for their company aiming to achieve (and outrun) the financial goals imposed by the market, the media - in this study concentrated on the Exame magazine - constitutes the driving force of the speech's propagation and production to the business entrepreneurs and executives. This work embraces as methodological resource the concept of Media's Representations (MR) that helped in the analysis of 25 editions and 57 published articles, between January and December of 2008, in the Exame magazine, that versed abut the economic crisis and the so called corporate values (accumulation of capital and profitability rising, value creation for shareholders and stockholders, social and profit responsibility, sustainable growth, innovation, competitive advantage, etc.). This investigation point to a paradoxical acting, but not incoherent by the Exame magazine, represented by the high-level company's executive, easing and subordinating the political speeches to the financial interests of the business media. The Exame magazine reenforces and spreads the so called company values and raises the executives and entrepreneurs to a individuals equipped with rare capacities and characteristics category, which are capable of helping the country to transpose the momentum, understood by many as history's biggest financial crisis, and continue their way to growth and, consequentially, the rising of companies' profit margin